Plastic Recycling as a Sustainable Waste Management Technology and Its Implications for Public Health: A Review - Waode Fitria Wulandari; Rahma Aulia. K; Shabilla Ananta Putri Baso; Talsa Karta Ballasari (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: The massive production of plastic waste poses serious challenges in waste management, making it a problem that must be addressed immediately. Plastic waste, often seen as an environmental threat, actually holds great potential to be recycled into high-value products. Objective: This research seeks to evaluate the effectiveness of various plastic recycling techniques as waste management strategies and to examine their implications for public health. Method: The study employs a Systematic Literature Review (SLR) with a descriptive design, aiming to collect and analyze articles accessible online. Results: The literature review indicates that plastic recycling provides dual benefits reducing environmental pollution and increasing economic value through added-value products such as plastic pellets, paving blocks, and ecobricks. Additionally, strategies like lean manufacturing and pyrolysis have been proven to enhance waste management efficiency. However, challenges remain, including technological limitations, high operational costs, and health risks associated with hazardous chemicals in plastics. Conclusion: Various measures have been implemented, ranging from recycling, applying lean manufacturing concepts, to developing environmentally friendly products, which not only help mitigate problems but also create new economic opportunities. Keywords: Technology, Waste, Impact, Plastic